The Future of ChatGPT in the Pakistani Education System: Transforming Learning and Teaching Dynamics - Sain, Zohaib Hassan; Thelma, Chanda Chansa (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
AI may change global education. ChatGPT may help Pakistan with overcrowded schools, teacher shortages, and resource limitations. According to a study, ChatGPT may enhance Pakistani education, teaching, and learning. This research suggests ChatGPT may boost Pakistani education. ChatGPT's influence on education, integrating concerns, and Pakistani education proposals are covered in the article. This research was quantitative and qualitative. Structured surveys of educators, students, and policymakers generated quantitative data, while semi-structured interviews were collected qualitatively. Urban-rural stratified sample. They evaluated qualitative data using regression, T-tests, and themes. Results demonstrate ChatGPT enhances Pakistani education. The survey showed teachers and students enjoyed ChatGPT's teaching and learning advantages. Testing showed ChatGPT enhanced student performance by 15%. According to qualitative research, ChatGPT may eliminate educational disparities in underprivileged areas despite concerns about digital infrastructure and teacher preparation. ChatGPT may enhance Pakistani education by improving learning, teaching, and access to high-quality education. It requires massive digital infrastructure expenditures, educator professional development, and government backing to succeed. Results impact politicians, educators, and technology. Education policymakers need frameworks like ChatGPT to use AI. AI and educator training must be culturally suitable. Pakistani educators get AI education research training and recommendations from this initiative.